Economic Behavior of Children and Adolescents - A First Survey of Experimental Economics Results - Matthias Sutter; Claudia Zoller; Daniela Glätzle-Rützler (Institute of Labor Economics (IZA), 2018)
About 15 years ago, economic experiments with children and adolescents were considered as an extravagant niche of economic research. Since then, this type of research has exploded in scope and depth. It has become clear that studying the development of economic behavior and its determinants is important to understand economic behavior of adults and to provide a basis for potential policy interventions with respect to economic behavior in childhood and adolescence. Given the huge increase of papers, we provide the first overview of economic experiments with children and adolescents. We focus on the following aspects: rationality of choices, risk preferences, time preferences, social preferences, cooperation, and competitiveness. All of these aspects are analyzed with respect to the influence of age and gender, and we also consider the role of socio-economic status or interventions.
Keywords: C91; D01; 330; competitiveness; risk preferences; time preferences; social preferences; survey; experiment; children; gender; age